Economics and the Limits of Optimization: Steps Towards Extending Bernard Hodgson’s Moral Science - Holdsworth, David Geoffrey (2012)
In this essay, my point of departure is Bernard Hodgson’s analysis of neo-classical economic theory and his demonstration that neo-classical economic thought is already a branch of normative theory. I undertake to broaden the demonstration by showing that other contemporary conceptions of economics are also irreducibly normative. The essay begins with an overview of Hodgson’s argument strategy, and a discussion of his thesis that economics is a moral science. This illustrates in what way moral presuppositions are at play as core principles that both positivist and normativist economics take for granted. My strategy is to show that alternative conceptions of economics, in particular Schumpeterian accounts of evolution/innovation, and orthodox versions of ecological economics, share with classical and neo-classical economics normative assumptions about the common good, extending Hodgson’s thesis to one about moral science. For then these assumptions (both moral and scientific) commit economics to unworkable notions of social and environmental optimization that ignore the pure historical contingency of physical, economic, social and cultural conditions. It is concluded that the relationship between facts and values must be fundamentally retheorized.
Keywords: ECOLOGICAL economics; Production theory; Innovation; Neo-classical economics; Optimization; Normative economics